Lipoxin A4 methyl ester attenuated ketamine-induced neurotoxicity in SH-SY5Y cells via regulating leptin pathway. (June 2023) - Zhang, Rui; Wang, Xueji; Xie, Ziyu; Cao, Tianyu; Jiang, Sufang; Huang, Lining
Abstract: Ketamine, the widely used intravenous anesthetic, has been reported to cause neurotoxicity and disturbs normal neurogenesis. However, the efficacy of current treatment strategies targeting ketamine's neurotoxicity remains limited. Lipoxin A4 methyl ester (LXA4 ME) is relatively stable lipoxin analog, which serves an important role in protecting against early brain injury. The purpose of this study was to investigate the protective effect of LXA4 ME on ketamine-caused cytotoxicity in SH-SY5Y cells, as well as the underlying mechanisms. Cell viability, apoptosis and endoplasmic reticulum stress (ER stress) were detected by adopting experimental techniques including CCK-8 assay, flow cytometry, western blotting and transmission electron microscope. Furthermore, examining the expression of leptin and its receptor (LepRb), we also measured the levels of activation of the leptin signaling pathway. Our results showed that LXA4 ME intervention promoted the cell viability, inhibited cell apoptosis, and reduced the expression of ER stress related protein and morphological changes induced by ketamine. In addition, inhibition of leptin signaling pathway caused by ketamine could be reversed by LXA4 ME. However, as the specific inhibitor of leptin pathway, leptin antagonist triple mutant human recombinant (leptin tA) attenuated the cytoprotective effect of LXA4 ME against ketamine-induced neurotoxicity. In conclusion, our findings demonstrated LXA4 ME could exert a neuroprotective effect on ketamine-induced neuronal injury via activation of the leptin signaling pathway. Highlights: Ketamine could induce decrease of cell viability, apoptosis, ER stress and inactivation of leptin pathway. LXA4 ME intervention reduced the damage effects of ketamine on SH-SY5Y cells. LXA4 ME could exert a protective effect on ketamine-induced neuronal injury via activation of the leptin signaling pathway.